IN-VITRO CYTOTOXICITY ACTIVITY OF MALAXIS RHEEDEI SW METHANOL EXTRACT AGAINST HELA CELL LINE AND MCF- 7 CELL LINE. - Haridas, Renjini (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Cancer is a group of diseases caused by loss of cell cycle control. Cancer is associated with abnormal uncontrolled cell growth. The study was aimed to evaluation of the anticancer activity of the Malaxis rheedei Sw. on the HeLa cell line and MCF- 7cell line. The whole plant part of the Malaxis rheedei methanolic extract were tested for its inhibitory effect on HeLa Cell Line and MCF- 7cell line. The cytotoxicity of Malaxis rheedei on HeLa cell and MCF- 7cell line were evaluated by the MTT assay. Malaxis rheedei methanolic extract has significant cytotoxicity effect on MCF- 7cell line in concentration range between 18.75 to 300 Âµg/ml by using MTT assay and study also showed that inhibitory action on HeLa cell line inconcentration range between 18.75 to 300 Âµg/ml by using MTT assay. Methanol extract ofÂ the whole plant part of Malaxis rheedei was found to be 7.3%, 16.6%,Â 25.4%, 36.3% and 47.1%toxic in HeLa cell line and 7.9%, 13.9%, 26%, 48.4% and 66.3% toxic in MCF- 7cell line. IC50 value of Malaxis rheedei on MCF- 7cell was Â 167.76Â Âµg/ml and IC50 value of Malaxis rheedei on HeLa Cell was not found by MTT assay. From the performed assay, methanol extract of these drug shows greater activity on MCF- 7cell line and little activity on HeLa cell line and that mean Malaxis rheedei can be used as anticancer activity. Keywords: Cytotoxicity Activity, MTT Assay, Malaxis rheedei Sw. , HeLa Cell Line, MCF- 7Cell Line.